PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA ALOKASI KHUSUS TERHADAP BELANJA MODAL PADA 19 KABUPATEN /KOTA PROVINSI SUMATERA BARAT PERIODE 2018-2020 - Febryandhie Ananda; Habiburrahman Habiburrahman (Sekolah Tinggi Pariwisata Mataram, 2023)
Capital Expenditures, which include regional expenditures, need to be taken into account because they are related towith the sustainable development of infrastructure and public facilities, spending low capital can affect the performance of various government agencies.Capital Expenditure is the main requirement in providing minimum standards local government public services. Therefore, this research aims to knowing the effect of Regional Original Income and Allocation Funds Specifically for Capital Expenditures in 19 districts/cities of West Sumatra Province in 2018-2020. Dataused in this study is annual secondary data that is time series obtained from the Revenue and Expenditure Budget Realization Report Regions in West Sumatra Province in 2018 to 2020. Based onThe results obtained show that local revenue and special allocation funds have a positive effect on capital expenditures in 19 districts/cities of West Sumatra province in 2018-2020.